Relationship between motivation, belief and intention, and participation in volunteerism among youth in Malaysia - Abdullah Sahimi, Nur Aishah Hamizah (2015)
Most studies have examined the direct relationship between motivation and youth participation in volunteerism. However, research on the relationship between motivation, belief and intention, and participation in volunteerism among youth in Malaysia is less examined. This study tested the relationship between motivation, belief and intention, and participation in volunteerism among youth in Malaysia. The objectives of the study was to determine (i) the level of motivation, belief, intention and participation of youth in volunteerism, (ii) the differences of youth participation in volunteerism by demographic profiles, (iii) the relationship between motivation, belief and intention of youth in volunteerism with their participation in volunteerism, and (iv) the most dominant factor influencing youth participation in volunteerism. This study adopts a descriptive and correlation research design to examine the direction and strength of the relationship among variables. Descriptive analysis that has been used to examine the level of youth motivation, belief, intention and participation were using mean, frequency and percentage. Pearson product moment correlation and Regression analysis were used to answer the study objectives. The sample of this study consisted of youth from various youth volunteer organizations in Malaysia. The study sample comprised of 342 youths selected using simple random sampling method. Data were gathered from 342 youths by using a self-administered questionnaire. To measure the research variables, this study used instruments established by few researchers. As for motivation variable, 27 items from Volunteer Functions Inventory (VFI) by Clary et al. (1998) were used. For the belief variable, this study used 35 instruments by several researcher including 20 items from Nickel (1998), 10 items from Furnham (1995) and 5 items from Law, Shek and Ma (2011). This study used also 10 items including 7 items from Wisner (2005) and 3 items from Law and Shek (2009) to measure volunteer intention. In order to measure volunteer participation, this research used 14 items including 8 items from Macon (2007) and 6 items from Marks (2009). For descriptive analysis, the result shows that most of the youth have high level of motivation, belief, intention and participation. For the t-test and ANOVA test, the result revealed that there is a significant difference in the level of participation in volunteerism based on religion and racial. Meanwhile, the results also showed that the three independent variables have significant relationships and highly positive correlated to the dependent variable. The analysis of this study proved that the motivation is the best predictor factor for predicting the dependent variable in this study. This study extends the existing literature on the role of motivation, belief and intention towards participation in volunteerism among youth in Malaysia and the findings of this study are expected to help and strengthen the formation of new models and concepts in the aspects of youth development behaviour. This study also suggests the future studies consider the broader population of youth volunteers from various associations in Malaysia. For the methodology this study suggests that future studies consider to make further research using qualitative method in order to produce more accurate and indepth study. Furthermore, this study hopes to provide knowledge especially for government and NGO organisations to give attention on volunteer motivation, belief and intention which could influence youth participation in volunteerism thereby enhance them to participate in more volunteer activities and programs.